(NpARAPSIHOLOGIQ (B/s - (NwINOKUROW(B, (NiGORX wLADIMIROWI^s ((NmOSKWA (B:s (Nast(B,s (NoLIMP(B,s (NaSTRELX(B,s, 2005)
(NkNIGA ZNAKOMIT ^ITATELQ S NEOBY^NYMI SPOSOBNOSTQMI ^ELOWEKA(B, (NSU]ESTWOWANIE KOTORYH STROGO(B-(NNASTROGO (B"(NZAPRE]ENO(B" (NNAUKOJ(B.s
(NnA OBL(B. (NAWT(B. (NNE UKAZANs
(NnA OBL(B. (NW PODZAG(B.: (NKN(B. (NZNAKOMIT ^ITATELQ S NEOBY^NYMI SPOSOBNOSTQMI ^ELOWEKA(B, (NSU]ESTWOWANIE KOTORYH STROGO(B-(NNASTROGO (B"(NZAPRE]ENO(B" (NNAUKOJs
Keywords: (NpSIHOLOGIQ (B- (NoSOBYE SOSTOQNIQ I QWLENIQ PSIHIKIs